"Learning English is the Single Most Important Thing": A Qualitative Analysis of the Linguistic Acquisition of Latino Minor League Baseball Players. Issue 2 (15th March 2023) - Gentile, Patrick C.
Abstract: This article seeks to understand how Latino Minor League Baseball (MiLB) players acculturate linguistically to life in the United States (US) while playing in the US South. To better understand how they acquire a knowledge of English, 24 current Latino MiLB players and one coach, who was also a former player, were interviewed. Questions were asked about their understanding of English, when they began learning English, and how they communicate with players and coaches from the US. It was found that knowing English is the most important way for players to acculturate to this new cultural environment and this was found through two main themes: the majority of acculturation is learning English and informal learning through baseball.